PENGARUH MODEL STAD BERBANTUAN VIDEO TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Saputra, Asep; Mashari, Ali; Herpratiwi, Herpratiwi (AHSANTA JURNAL PENDIDIKAN, 2024)
This research aims to determine the influence of the video-assisted student teams achievement division type cooperative learning model on mathematics learning outcomes for class VA at SD Muhammadiyah 3 Panjang, Bandar Lampung City. This research is quantitative research in the form of one group pretest-posttest. The population this study were all class V students at SD Muhammadiyah 3 Panjang, Bandar Lampung City. The sampling technique used purposive sampling, while the data collection technique used tests and the data analysis technique used was the paired T test. The results of the research are shown by the results of the t-test with a Sig. (2-tailed) value of 0.000 < 0.05. So it can be concluded that there is an influence of the Video-Assisted Student Teams Achievement Division Type Cooperative Learning Model on the mathematics learning outcomes of class VA students at SD Muhammadiyah 3 Long Bandar Lampung City.